2005
DOI: 10.4269/ajtmh.2005.72.201
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Patterns of and Risk Factors for Seropositivity for Dengue Infection

Abstract: Spatial patterns of and risk factors for seropositivity of dengue infection were studied in three sites in northern Thailand. A survey was conducted in 2001 among 1,750 persons. Potential risk factors for dengue infection were measured by questionnaire and IgM antibodies against dengue were detected by an enzyme-linked immunosorbent assay. The role of landscape as a risk factor was studied using land cover maps and a geographic information system. Logistic regression identified risk factors for dengue seroposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
80
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 19 publications
7
80
0
4
Order By: Relevance
“…40 It is intriguing that other studies did not find an association with sex; cultural determinants in these communities could explain this finding. 37,[41][42][43] In regard to occupation, when adjusting by age, locality, and sex, independent workers, senior citizens without salary, disabled individuals, retirees, and housewives were associated with a higher seroprevalence compared with students. In addition, the relationship between seroprevalence and housewife status has previously been reported in Singapore, and these observations may have two explanations.…”
Section: Discussionmentioning
confidence: 99%
“…40 It is intriguing that other studies did not find an association with sex; cultural determinants in these communities could explain this finding. 37,[41][42][43] In regard to occupation, when adjusting by age, locality, and sex, independent workers, senior citizens without salary, disabled individuals, retirees, and housewives were associated with a higher seroprevalence compared with students. In addition, the relationship between seroprevalence and housewife status has previously been reported in Singapore, and these observations may have two explanations.…”
Section: Discussionmentioning
confidence: 99%
“…• Local determinants Dengue should not be considered a poverty-related disease because it affects wealthy neighbourhoods as well, although the magnitude of risk can be moderated by the use of housing materials such as screens in doors and windows 27,28 . In Taiwan, it was estimated that 63% of dengue infections could be eliminated if everyone lived in adequately screened homes 29 .…”
Section: • Global Determinantsmentioning
confidence: 99%
“…By comparing three locations of serology surveys, it is found that females aged more than 30 years old were significantly correlated with the seropositivity of 1,750 participants in the study population [16]. Females has are at a higher risk compared to males was found by another study in Thailand by the same researchers [17].…”
Section: Discussionmentioning
confidence: 70%
“…However, in terms of action (practice), respondents in Medan Baru performed much better. Indeed, ignorance of dengue was found to double the seropositivity risk in northern Thailand [16]. Fighting against dengue requires knowledge and affirmative actions.…”
Section: Discussionmentioning
confidence: 99%